Smart Employee Tracking - Sreekantha kumar V P, Praveen Prabhu C, Sathish M, Mohammed Fazil R (International Journal of Advanced Science and Technology, 2020)
As the number of employees working in an organization have been expanding into huge numbers and it has been difficult to keep track and locate the employee. Smart Employee tracking is a mobile application that is used to track the current location of the employee in the campus. This paper describes a real-time system for employee tracking and . This app provides the platform to search the employees within the college campus. With the help of GPS tracker, the employee’s current location can be tracked through the mobile app. The GPS tracker plays a vital role by sending the latitude and longitude coordinates to the server and the app fetches data from the server and the employee location will be determined. It runs on both the Android and iOS platform and uses firebase for storing and retrieving data. It helps in saving a life when the employee gets stuck somewhere or goes hidden for a very long time inside the building. The objective of the system is to track and locate the employee current location inside the building which saves the monitoring time. This system will considerably reduce the time involved in the manual search.